Effects of sleep duration and quality on external workload in womens collegiate lacrosse athletes - Sutton, P. J.; Mumford, P. W.; Cintineo, H. P.; Sunderland, K. L. (International Journal of Exercise Science Conference Proceedings, 2024)
The importance of sleep in the recovery process is well-established. Exploring the potential impact of athletes' recovery on the subsequent day's external workload during training adds a critical insight into the relationship between sleep and athletic performance. The understanding of recovery and external workload is particularly important for enhancing an athlete`s well-being and performance.